2020
DOI: 10.1128/mbio.01134-19
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plasmodium falciparum Kelch 13 Protein Mutations in P. falciparum Populations from Northeastern Myanmar in Mediating Artemisinin Resistance

Abstract: Mutations in the Plasmodium falciparum Kelch 13 (PfK13) protein are associated with artemisinin resistance. PfK13 is essential for asexual erythrocytic development, but its function is not known. We tagged the PfK13 protein with green fluorescent protein in P. falciparum to study its expression and localization in asexual and sexual stages. We used a new antibody against PfK13 to show that the PfK13 protein is expressed ubiquitously in both asexual erythrocytic stages and gametocytes and is localized in puncta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 84 publications
3
93
0
1
Order By: Relevance
“…Our results suggested that few if any interactions were specific to either the WT or mutant K13 isoforms. Many of our candidate K13-associated proteins were also observed in a recent study that used GFP-Trap beads to affinity purify GFP-K13 followed by LC/MS-MS [53]. These proteins included S-adenosylmethionine synthetase (the most abundant protein in our dataset), elongation factor 2, and plasmepsin II.…”
Section: Plos Pathogensmentioning
confidence: 52%
See 2 more Smart Citations
“…Our results suggested that few if any interactions were specific to either the WT or mutant K13 isoforms. Many of our candidate K13-associated proteins were also observed in a recent study that used GFP-Trap beads to affinity purify GFP-K13 followed by LC/MS-MS [53]. These proteins included S-adenosylmethionine synthetase (the most abundant protein in our dataset), elongation factor 2, and plasmepsin II.…”
Section: Plos Pathogensmentioning
confidence: 52%
“…II WT respectively (S5 Table). By comparison, a very recent study using K13-specfic polyclonal antiserum reported a PCC value of 0.58 between WT K13 and BiP [53]. Interestingly, following DHA treatment, mutant and WT parasites showed significant differences at 12h post drug pulse (Fig 3E and S5C Fig).…”
Section: K13 Partially Co-localizes With the Er Chaperone Bip But Notmentioning
confidence: 72%
See 1 more Smart Citation
“…Nevertheless, the other PB K13 mutations tested herein appear to directly reflect the impact of the equivalent mutations in PF. Both PB F458I (this study) and PF F446I K13 mutants are fitness neutral (56) and do not enhance RSA survival in vitro (56,57), yet carry ART protective phenotypes in vivo (58)(59)(60). Furthermore, PB M488I K13 mutants display a significant growth defect that has not yet been characterized in the PF equivalent (M476I) and might explain its relative scarcity in SEA (61,62).…”
Section: Discussionmentioning
confidence: 83%
“…14 Meanwhile, parallel functional and localisation studies have also revealed that Kelch13 co-localises with multiple UPR components, proteins specific to the ER and mitochondria as well as intracellular vesicular trafficking Rab GTPases. [15][16] Central to the activity of the UPR is the ubiquitin proteasome system (UPS), a conserved eukaryotic pathway that plays a role in protein homeostasis by degrading unfolded proteins. Under ART pressure, activity of the UPS is more upregulated in Kelch13 mutant parasites compared to wild type while UPS inhibitors have been shown to synergize ART action suggesting that this pathway could be selectively targeted to overcome ART resistance.…”
Section: Introductionmentioning
confidence: 99%